Immobilization of cadmium in soil using magnetic biochar derived from Eichhornia crassipes - Chaiyaraksa, Chompoonut; Lokham, Nongnapa; Kuikrong, Rawisara; Artsanapaiboon, Sangarun (My University, 2020)
Heavy metal contamination in an environment is a critical problem in Thailand that needs to be addressed urgently, particularly contaminated soil. This research aims to study the adsorption of cadmium ion by unmodified biochar and sodium dodecyl sulfate modified magnetic biochar (SDS-MB) derived from Eichhornia Crassipes. The adsorbent and soil characteristics were determined. Observed by scanning electron microscope (SEM), the surface of unmodified biochar (B) was smoother than SDS-MB. The X-ray diffractometer (XRD) pattern showed peaks for iron oxide. The values of point of zero charge (pHPZC) and acid neutralization capability (ANC) were 3 and 1000.3 meq/kg, respectively. The greatest adsorption of cadmium occurred when the pH of the wastewater was 8. The adsorption reached equilibrium within 1 h. It followed Freundlich, Temkin, and Dubinin-Radushkevich isotherm model and the pseudo-second-order kinetic. SDS-MB was mixed with sandy clay loam soil (pH 7.87) contaminated with cadmium 50 mg per kilogram soil at the ratio of 0-5%. The results from the extraction with ethylenediaminetetraacetic acid (EDTA), ammonium acetate, calcium chloride, diethylene triamine pentaacetic acid (DTPA), and sequential extraction method indicated that 5% mixing ratio showed the best ability to reduce cadmium movement in the soil. Cadmium in a form that bound to oxide and a form that bound to organic matter significantly increased.
Keywords: Cadmium; Eichhornia crassipes; Magnetic biochar; Sodium dodecyl sulfate; Soil remediation